Governança Corporativa e sua Relação com a Divulgação da Natureza e Extensão dos Riscos Relacionados aos Instrumentos Financeiros - Danielle Gonçalves Silva (2020)
With the increase in the demand for risk information, caused mainly by the various global economic crises, the accounting regulatory bodies directed their attention to the elaboration of rules that would improve the disclosure of corporate risks of the entities, mainly those related to financial instruments, considered of great relevance for the capital market. The search for factors that influenced the disclosure of information led to the finding that companies that adopt good corporate governance practices provide more relevant information to their shareholders and interested parties. In this sense, it was identified that internal characteristics of corporate governance were directly related to the practices of disclosure of risk information. Considering these aspects, this research aimed to identify the determinants of corporate governance that influenced the disclosure of the nature and extent of exposure to risks arising from financial instruments. The study sample was made up of publicly traded companies listed on B3 (Brazil, Bolsa and Balcão), which belonged to some listing segment (Novo Mercado, Nível 1, Nível 2, Bovespa Mais and Bovespa Mais Nível 2) and which did not were from the financial sector. The analyzed period refers to the years 2016 to 2018. The approach to the research problem was considered quantitative, using the econometric model of Generalized Least Squares. As for the research objectives, it was considered as descriptive, using the bibliographic, documentary and ex post facto strategy. The results of the regression analysis showed that all variables used to measure the determinants of corporate governance (board size, board independent, ownership concentration, CEO duality and audit committee) were significant to explain the level of disclosure of the nature and extent of exposure to risks arising from financial instruments. With the exception of the board independent and CEO duality variables, which negatively influence the level of disclosure, the other variables have a positive influence. Regarding the control variables (firm size, belonging to the Novo Mercado segment, return on assets, leverage and year 2018), all were also significant to explain the level of disclosure. The variables firm size and belonging to the Novo Mercado segment positively influence the level of disclosure, and the other variables have a negative influence. This study contributes to the issue of disclosure of risk information by Brazilian companies, as it broadly addresses the mandatory disclosure of the nature and extent of exposure to risks arising from financial instruments, considering both the current standard NBC TG 40 (R3) and the previous one. Additionally, it deepens the knowledge regarding the association of this type of disclosure with the corporate governance mechanisms used in Brazil.